Rapid Synthesis of a Long Double-Stranded Oligonucleotide from a Single-Stranded Nucleotide Using Magnetic Beads and an Oligo Library. - Sumate Pengpumkiat; Myra Koesdjojo; Erik R Rowley; Todd C Mockler; Vincent T Remcho (PLoS ONE, 2016)
Chemical synthesis of oligonucleotides is a widely used tool in the field of biochemistry. Several methods for gene synthesis have been introduced in the growing area of genomics. In this paper, a novel method of constructing dsDNA is proposed. Short (28-mer) oligo fragments from a library were assembled through successive annealing and ligation processes, followed by PCR. First, two oligo fragments annealed to form a dsDNA molecule. The double-stranded oligo was immobilized onto magnetic beads (solid support) via streptavidin-biotin binding. Next, single-stranded oligo fragments were added successively through ligation to form the complete DNA molecule. The synthesized DNA was amplified through PCR and gel electrophoresis was used to characterize the product. Sanger sequencing showed that more than 97% of the nucleotides matched the expected sequence. Extending the length of the DNA molecule by adding single-stranded oligonucleotides from a basis set (library) via ligation enables a more convenient and rapid mechanism for the design and synthesis of oligonucleotides on the go. Coupled with an automated dispensing system and libraries of short oligo fragments, this novel DNA synthesis method would offer an efficient and cost-effective method for producing dsDNA.